2000
DOI: 10.4018/joeuc.2000100102
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gender and Experience on User Confidence in Electronic Mail

Abstract: While electronic communication is advancing rapidly in the organizational context, there remain a considerable number of participants who, for one reason or another, lack the skills and/or confidence to make the medium a pervasive and ubiquitous tool. This paper examines a network of factors that influence attitudes about computer utilization and user confidence in electronic mail (e-mail). A conceptual model of user confidence in e-mail was developed based on the results of a previous study, refined after a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…However, if the variable of confidence in computer usage is removed, both men and women were equally reliant on email in the workplace. These findings agree with a study by Hoxmeier et al [5], which identified gender and experience as two factors affecting an individual's ubiquitous and pervasive use of email. The study found that experience of IT positively affects an individual's perceived confidence in the use of email, and that women lacking a strong IT background perceive themselves as less confident in use of email than men of similar backgrounds; however, computing skills and experience using IT and email neutralize this gender difference in confidence.…”
supporting
confidence: 92%
“…However, if the variable of confidence in computer usage is removed, both men and women were equally reliant on email in the workplace. These findings agree with a study by Hoxmeier et al [5], which identified gender and experience as two factors affecting an individual's ubiquitous and pervasive use of email. The study found that experience of IT positively affects an individual's perceived confidence in the use of email, and that women lacking a strong IT background perceive themselves as less confident in use of email than men of similar backgrounds; however, computing skills and experience using IT and email neutralize this gender difference in confidence.…”
supporting
confidence: 92%
“…Second, the root mean residual (RMR) and the root mean square error of approximation (RMSEA) should be less than 0.05 (Jöreskog and Sörbom, 2002;Bentler, 1990) or the limit value should be less than 0.08 (Byrne, 2001). Finally, the ratio of chi-square values to freedom degrees (2/ df) should be less than 3.0 (Hoxmeier et al, 2000). The scale reliability was assessed by item reliability measured by individual reliability coefficient (R2).…”
Section: Methods Of Analysismentioning
confidence: 99%
“…No obstante, se puede manifestar que tan solo en dichos aspectos relacionados con las TIC se han obtenido diferencias significativas. Este último dato también es coherente con otros estudios que no encuentran diferencias estadísticamente significativas entre hombres y mujeres (Adebanjo, 2004;Hoxmier, Nie y Purvis, 2000;Tekinarslan, 2008) en actitudes hacia las TIC y otros aspectos relacionados con el conocimiento y uso de los ordenadores. Asimismo, también se han encontrado diferencias estadísticamente significativas en lo que a la percepción y actitudes hacia las TIC en función de la especialidad se refiere.…”
Section: Conclusiones Y Discusiónunclassified